The potential roles of circular RNAs in osteonecrosis of the femoral head - Zhao, Jun (Mol Med Rep, 2020)
Circular RNAs (circRNAs) are categorized as non-coding RNAs that, unlike widely known canonical linear RNAs, form a covalently closed continuous loop without 5′ or 3′ polarities, which enables them to resist digestion by RNA exonucleases. Although the functions of circRNAs remain largely unknown, accumulated evidence has demonstrated that circRNAs can act as microRNA sponges, which allows them to regulate numerous biological processes and disease mechanisms, including apoptosis, angiogenesis, invasion, metastasis and stem cell differentiation. Although research into circRNAs is in its infancy, studies have identified critical roles for circRNAs in the initiation and progression of disease. The present study delineated the characteristics and functions of circRNAs, and focused on the potential relationship between circRNAs and osteonecrosis of the femoral head (ONFH). CircRNAs represent a novel avenue for studying the mechanisms underlying ONFH as well as possible treatments.